Kinetics and mechanisms of CrAlN coating oxidation process - Tan, Benit Zhi Wei. (2010)
Thin wear-resistant hard coatings are widely applied on cutting tools to improve lifetime and performance. TiAlN has been successfully commercialized because of its oxidation resistance and hardness. A new generation of hard coating, CrAlN have been reported exhibiting even higher oxidation resistance than TiAlN. Several studies on microstructure and mechanical properties of CrAlN have been published but the oxidation behaviour has not been significantly explored. Understanding of the oxidation mechanisms and growth kinetics requires a series of suitable characterization techniques. In this work, two ternary hard coatings, CrAlN and TiAlN (Al/Ti or Al/Cr atomic ratio around 1:1), were deposited on stainless steel substrates by lateral rotating cathode arc technique. The as-deposited coatings were annealed in ambient atmosphere at different temperature (700-1000 °C) for 1-16 hrs. The changes in surface morphology, chemical composition, and microstructure were analyzed by Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray spectroscopy (EDX) and X-ray Diffraction (XRD) experiments. Composition depth profile of the coatings was measured by Glow Discharge Optical Emission Spectroscopy (GDOES). It was found that among the two ternary coatings, CrAlN has a significantly better oxidation resistance than TiAlN. TiAlN coating started to oxidize at 700 °C and it was almost fully oxidized and delaminated at 1000 °C. Oxidation rate of CrAlN coating was slower and after annealing at 1000 °C for 16 hrs, only about 54 at.% of oxygen was detected and the coating showed no delamination. The parabolic oxidation rate constant of TiAlN was found to be 2x10-17 m2/s at 700 °C and increased to 7x10-16 m2/s at 900 °C. Rate constant for CrAlN remained around 2x10-19 m2/s at 700 °C and 800 °C and increased to 1x10-17 m2/s at 1000 °C. Depth profile analysis indicate that oxidation of TiAlN produced an outer layer of Al2O3 followed by a layer of TiO2 and oxynitride. Out-diffusion of aluminium controls the formation of the outer oxide layer. TiO2 and oxynitride below indicate an efficient trapping of titanium below the Al2O3 layer. In contrast, the oxidation mechanism of CrAlN was very different from TiAlN. Initial oxidation commenced by reacting with in-diffusing oxygen to form a layer of Cr2O3 and Al2O3 scale, releasing nitrogen. Extended oxidation caused out-diffusion of chromium and led to formation of pure Cr2O3 grains on the outermost layer. This protective oxide scale prevents decomposition of CrAlN indicating a very promising applicability of this coating for high temperature applications.